Representation of Virginity Value in the Surprised Marriage Series (Roland Barthes Semiotics Analysis) - Gratxya Pattimahu; Danang Trijayanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Film has a great influence in shaping people's mindsets. The message or value contained in the film is certainly able to influence the audience both cognitively, affectively and conatively. Webseries Shocked Marriage is a series that tells the story of Lalita who is considered to have lost her virginity due to an accident. By using a qualitative approach with the perspective of Roland Barthes' semiotic theory to understand the denotative, connotative meanings, and myths of virginity contained in the Kaget Nikah webseries. The research data collection technique was obtained from the Shocked Marriage series by taking screenshots of images as primary sources and then classifying categories and linking them with Barthes' semiotic analysis. And secondary sources are obtained from books, printed and electronic articles, scientific journals and theses related to this research. The results show that the concept of virginity circulating in the community is interpreted the same way in the Shocked Marriage webseries. the membrane of blood and blood that comes out on the first night is interpreted as a symbol of female virginity. The blood membrane is used as a benchmark for a woman's virginity status with various characteristics, forms, causes, and others. The public perception of the integrity of the blood membrane that has been constructed is just a myth that appears and develops in people's lives.